2003
DOI: 10.1034/j.1600-0544.2003.246.x
|View full text |Cite
|
Sign up to set email alerts
|

Using three‐dimensional imaging to assess treatment outcomes in orthodontics: a progress report from the University of the Pacific

Abstract: Past research in integrated three-dimensional (3D) craniofacial mapping at the Craniofacial Research Instrumentation Laboratory (CRIL) of the University of the Pacific is summarized in narrative form. The advantages and limitations of recent commercial developments in the application of cone beam geometry volumetric X-ray scanners in dentistry and surface digital mapping of study casts are discussed. The rationale for methods currently in development at CRIL for merging longitudinal information from existing 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 7 publications
(10 reference statements)
0
19
0
5
Order By: Relevance
“…It seems to be that the fullest understanding of growth and treatment processes could be obtained by integrating data from these several sources into a continuous integrated system, to produce an integrated stereo model that begins to meet the needs of clinical orthodontists (Baumrind et al 2003).…”
Section: Perspectivesmentioning
confidence: 99%
“…It seems to be that the fullest understanding of growth and treatment processes could be obtained by integrating data from these several sources into a continuous integrated system, to produce an integrated stereo model that begins to meet the needs of clinical orthodontists (Baumrind et al 2003).…”
Section: Perspectivesmentioning
confidence: 99%
“…[20] This started the era of the use of 3D imaging in dental disciplines and particularly in orthodontics, e.g., Upper airway evaluation,[21] periodontal evaluation for implant loading,[22] evaluating surgical outcome,[2324] and assessing orthodontic treatment outcomes. [25] In a literature review done by De Vos for 86 articles in the clinical application of CBCT in the oral and maxillofacial region, it was found that 16% of these articles are related to orthodontics. [26] The wide application of 3D imaging in orthodomtics can be due to the accurate 3D representation of a subject, low radiation and the possibility of conversion from 3D images to two-dimensions (2D) images when required.…”
Section: Introductionmentioning
confidence: 99%
“…One is the high cost of scanning hardware, but even more important drawbacks are their frequently cumbersome use and the lack of efficient 3D analysis software, standardization, and easy calibration. These obstacles, however, will be overcome eventually (e.g., Baumrind et al, 2003). Meanwhile, one can ask if there are situations where 2D measurements would be sufficient and would provide a trade-off between accuracy on the one hand and simplicity, cost, and time on the other.…”
mentioning
confidence: 97%